(3cJGH GHdhfjhS aj GdeNQhWGJs - ((3Hfj ehSi (B( (3eMeO hGdMSf hCMeOs
(3ChdgG (B:s
(3HYO GdHSedI Gf Yde bWhY GdeNQhWGJ aj CTQa GdefGRd hGYdj GdeQGJH ef Yde GdgfOSI hcGf GdbOeGA s
(3BNQgG (B:s
(3ef BNQ GdehLhO Hg Ydi LejY GdGMhGd GdYehO efg Gdj fbWI fSHI SWM s
(3HgG fXGe GdJYbjHIs
(3jfbU efg GdebGdI GdKGefIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs